1993
DOI: 10.1093/ije/22.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Serum Retinol, β-Carotene, α-Tocopherol and Cholesterol in Healthy French Children

Abstract: Age- and sex-specific reference intervals of data derived from a healthy paediatric population are presented for retinol, beta-carotene, alpha-tocopherol, cholesterol and related proteins in serum. Age was an important covariate for the micronutrient concentration values. Retinol was highly correlated with alpha-tocopherol and cholesterol. Strong correlation was found with both beta-carotene and cholesterol. Serum levels were considered for their appropriateness as indicators of micronutrient status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 0 publications
5
15
3
Order By: Relevance
“…The serum levels of vitamin A and β-carotene in the control group were similar to the levels previously reported (18,19). Similarly, the level of serum cholesterol and triglycerides in the control group was also in agreement with earlier published reports (20,21).…”
Section: Discussionsupporting
confidence: 92%
“…The serum levels of vitamin A and β-carotene in the control group were similar to the levels previously reported (18,19). Similarly, the level of serum cholesterol and triglycerides in the control group was also in agreement with earlier published reports (20,21).…”
Section: Discussionsupporting
confidence: 92%
“…Only 6% of them had values below 0.53 µmol/l (300 µg/l), which has been proposed as the lower limit of plasma β-carotene concentration to fulfill provitamin A function [22]. In our study group more than 50% of the children did not reach this level, and -as in the study by Malvy et al [15] -low β-carotene levels were especially common in girls between 10 and 14 years. However, retinol requirements in German children are mainly met by direct intake and all plasma retinol levels in our study group were in the normal range (data not shown).…”
Section: Discussioncontrasting
confidence: 40%
“…A tendency towards higher levels of αand β-carotene in younger children was also found in France, but these children had on an average higher levels of β-carotene [15]. Only 6% of them had values below 0.53 µmol/l (300 µg/l), which has been proposed as the lower limit of plasma β-carotene concentration to fulfill provitamin A function [22].…”
Section: Discussionmentioning
confidence: 93%
“…These were considerably higher than the median serum retinol concentrations in comparable age groups in the Tanzanian school-age children. Similar to other school-age populations, the distribution of serum retinol concentrations in primary school-age children increased with age (P ¼ 0.027; Table 2) (Lewis et al, 1990;Malvy et al, 1993).…”
Section: Discussionsupporting
confidence: 67%